Analisa Transparansi Pendapatan Asli Daerah (PAD) Terhadap PDRB Kabupaten Bangkalan Dalam Upaya Meningkatkan Kepercayaan Masyarakat Dan Tax Complience - Sari, Silvia; Iqrimah, Rafika; Djasuli, Mohamad (Peneliti.net, 2024)
PAD is obtained from regional taxes, regional levies, separated regional wealth management results and other legitimate PAD. In 2018, Bangkalan Regency's highest regional tax revenue contribution to PAD was with a percentage of 20.6%, where in that year the total realization was 239,513,792,916.41. Bangkalan district's GRDP contribution was highest in 2018 with a figure of 4.22% and decreased in 2019 to 1.03%. Through the results of E-Views calculations, it was found that the probability value (f-statistic) of GRDP was 0.571 (>0.005) which means that PAD does not have a significant influence on GRDP. According to research (Ketut, 2013) it is said that based on PAD calculations it does not have a significant influence because there are several other factors such as the level of welfare, HDI (human development index), level of tax compliance, awareness of tax payments. The regression coefficient value of -0.299 is negative, which means that if the GRDP variable decreases, the PAD variable will also decrease. Based on the OECD model, it can be seen that taxpayer compliance behavior varies greatly. Each level of tax compliance can be responded to with a compliance strategy.